2016
DOI: 10.5604/20831862.1189767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultra-endurance exercise on left ventricular performance and plasma cytokines in healthy trained men

Abstract: The purpose of this study was to investigate the effect of ultra-endurance exercise on left ventricular (LV) performance and plasma concentration of interleukin (IL)-6, IL-10, IL-18 and tumour necrosis factor alpha (TNF-α) as well as to examine the relationships between exercise-induced changes in plasma cytokines and those in echocardiographic indices of LV function in ultra-marathon runners. Nine healthy trained men (mean age 30±1.0 years) participated in a 100-km ultra-marathon. Heart rate, blood pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Although a post‐exercise periostin release was likely, as also observed with other pro‐inflammatory proteins, the acute bout of exercise was not observed to have any such influence on median periostin levels in serum or EBC. However, in individual athletes, periostin serum or EBC concentrations following exercise were dramatically (several‐fold) higher or lower than baseline levels in controls.…”
Section: Discussionmentioning
confidence: 62%
“…Although a post‐exercise periostin release was likely, as also observed with other pro‐inflammatory proteins, the acute bout of exercise was not observed to have any such influence on median periostin levels in serum or EBC. However, in individual athletes, periostin serum or EBC concentrations following exercise were dramatically (several‐fold) higher or lower than baseline levels in controls.…”
Section: Discussionmentioning
confidence: 62%
“…Il-6 (5.4 % increase), which has pleiotropic anti-and pro-inflammatory effects depending on its site of production, had largely returned to baseline. Il-6 increases dramatically when measured acutely after endurance exercise with a recent study describing an 88-fold increase immediately after and a 69fold increase 90 min after a 100 km ultra-marathon [18]. In the same study, IL-1β and TNF-α had largely returned to baseline after 90 min [18].…”
Section: Discussionmentioning
confidence: 81%
“…To investigate the effects in IL‐10 behavior after acute exercise, the results were grouped according to the type of exercise. Four articles studied the effects of exercise and IL‐10 on strength (Agostinete et al, ; Gerosa‐Neto et al, ; Peake, Nosaka, Muthalib, & Suzuki, ; Rossi, Gerosa‐Neto, Zanchi, Cholewa, & Lira, ), three on continuous running versus intermittent running performed on treadmill (Cabral‐Santos et al, ; Dorneles et al, ; Ghafourian, Ashtary‐Larky, Chinipardaz, Eskandary, & Mehavaran, ), one on cycling ergometer (Cullen, Thomas, Webb, & Hughes, ;) and four on strenuous exercise – lasting at least 3 hr of outdoor long distance race (which the runners were allowed to choose their own speed) associated or not to other type of exercise (Comassi et al, ; Kaoru, Suzuki, Yoshitani, Shiraishi, & Kometani, ; Krzemiński et al, ; Nickel et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Krzemiński et al () showed that well‐trained young men who completed a 100 km ultra‐endurance exercise reported significant increases in plasma IL‐6, IL‐10, IL‐18, and TNF‐α concentrations immediately after the event. At 90 min of the recovery period, plasma concentrations of IL‐6 and IL‐10 were still higher ( p < 0.05) than before exercise, whereas plasma TNF‐α did not differ significantly from the resting pre‐exercise values.…”
Section: Discussionmentioning
confidence: 99%